TEACHERS' EXPERIENCE IN USING ICE BREAKING TO INCREASE EARLY CHILDHOOD STUDENTS' MOTIVATION IN ENGLISH LEARNING - Ziyan Annisah; Ghaniyah Nur Azeeza Putri; Syakira Desiya (Adisam Publisher, 2025)
The present study aims to explore and analyse teachers' views and experiences in using ice breaking as a strategy to increase motivation to learn English in early childhood. Ice-breaking activities are recognised as a pivotal component in establishing an conducive learning environment, enhancing student engagement, and mitigating affective barriers. The present study employs a qualitative descriptive approach, with data collected through an open-ended questionnaire distributed via Google Forms to 30 teachers from preschool to junior high school levels who have experience using ice-breaking activities. The findings indicate that the vast majority of teachers have incorporated ice-breaking activities into their lessons, with the most prevalent forms of activities being songs, physical games, and quizzes. Teachers have perceived the efficacy of ice-breaking activities in enhancing students' focus, active participation, and enthusiasm. Nevertheless, challenges such as time constraints, a paucity of activity variety, and classroom management persist. Furthermore, these findings lend further support to the theory of the importance of a positive classroom climate, intrinsic motivation, and the reduction of affective barriers in language learning. Furthermore, teachers' perceptions of the efficacy of ice-breaking activities have been shown to significantly influence their successful implementation. The present study concludes that ice-breaking activities are a strategic element in early childhood English language learning, with their success heavily dependent on teachers' preparedness and creativity.